2021
DOI: 10.1021/acs.chemmater.1c02803
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Interfaces in Solid-State Batteries Using Interfacial Thermochemistry and Band Alignment

Abstract: Solid-state lithium ion batteries have enhanced thermal stability compared to batteries using liquid electrolytes. Although their practical implementation is limited by undesired side reactions between the electrode and electrolyte, different modification strategies have been proposed to stabilize these reactive interfaces. These approaches have been primarily based upon bulk materials properties, however, which may not necessarily be representative of the chemistry at the solid/solid interface. Herein, first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…In our previous study, we discovered that unsubstituted LLTO is a metastable phase and secondary phases are needed to stabilize it such phase is TiO 2 . Recently, Warburton et al in their computational study similarly found that LLTO is metastable . In the current study, we conclude that a number of substitutions stabilize the perovskite, enabling single-phase perovskites to form.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…In our previous study, we discovered that unsubstituted LLTO is a metastable phase and secondary phases are needed to stabilize it such phase is TiO 2 . Recently, Warburton et al in their computational study similarly found that LLTO is metastable . In the current study, we conclude that a number of substitutions stabilize the perovskite, enabling single-phase perovskites to form.…”
Section: Resultssupporting
confidence: 60%
“…20 Recently, Warburton et al in their computational study similarly found that LLTO is metastable. 22 In the current study, we conclude that a number of substitutions stabilize the perovskite, enabling single-phase perovskites to form.…”
Section: Resultsmentioning
confidence: 50%
“…Figure b compares the reported diffusion coefficient data attained by MD simulations ,,, , with the present experimental data. With the exception of the earliest data, all the reported results agree with our experimental data within one order of magnitude.…”
Section: Resultsmentioning
confidence: 63%
“…Comparison of the diffusion coefficients of lithium lanthanum titanates with literature data and the present data. (a) Experimental diffusion coefficients using neutron radiography ( D NR ), PFG-NMR, , and QENS and (b) classical MD simulations ( D MD ), ,, AIMD simulations ( D AIMD ), and machine learning interatomic potential MD simulations ( D MLMD ) …”
Section: Resultsmentioning
confidence: 99%
“…15,16 Nonetheless, the thermodynamically stable potential range is limited, and first-principles calculations predict an electrochemical phase stability window of 1.75-3.7 V vs Li metal. [17][18][19] Consequently, application of more than 2 V bias to Li-ion blocking electrodes may result in electrochemical decomposition of the electrolyte. These first-principles calculations predict O 2 evolution and formation of La 2 Ti 2 O 7 and Li 4 Ti 5 O 12 at the anode, whereas Li-rich phases that contain Ti 3+ , like Li 7 Ti 11 O 24 , La 2 Ti 2 O 7 and Li 4 Ti 5 O 12 are the most stable phases at the cathode.…”
mentioning
confidence: 99%